Metryki i ich zastosowanie w metodach wielokryterialnych wspomagających podejmowanie decyzji - Trzęsiok, Joanna; Trzęsiok, Michał (Metrics and Their Applications to the Multicriteria Optimization Supporting the Decision Making process, 2006)
One of the most common approaches in the multicriteria optimization is called "the distance approach". It can be used in a discrete case. The optimal solution is the one which is the closest, in the sense of a given distance function, to the pattern. The pattern is a theoretical (ideal) solution set by the decision maker. The essential role is played by the distance function which is simply the metric in the decision space.In teaching mathematics the presentation of an example illustrating this method allows to stress the importance of choosing the metrics and comparing their properties. The paper focuses on the issue of controlling the criteria substitution in particular.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1117, s. 180-187